A NOTE ON THE POTENTIAL USE OF MORINGA OLEIFERA TREE AS ANIMAL FEED - A. A, Mabruk; H. N, Talib; M. A, Mohamed; A. H, Alawad (Journal of Veterinary Medicine and Animal Production, 2022)
Samples of different morphological parts of Moringa oleifera (seeds, flowers, pods, leaves, stems and whole plant) were analyzed for their chemical components and in situ digestibility values. The results revealed that the crude protein contents of those parts varied between 97.1-348.0 g/kg DM suggesting them as a good source of protein for feeding animals. Furthermore the high contents of fat in seeds (388.0 g/kg DM) suggesting that such seeds could be used as a source of edible oils